The attitude of the students of the Academy of Physical Education to smoking habits - Wójtowicz-Chomicz, Katarzyna; Czeczuk, Anna; Huk-Wieliczuk, Elżbieta; Borzęcki, Andrzej (Polish Journal of Public Health, 2015)
Introduction. Poland is among the top ten countries of the European Union displaying the highest intensity of smoking. Aim. To evaluate the frequency and intensity of smoking, the strength of nicotine addiction and the motivation to discontinue smoking, among students of the Academy of Physical Education. Material and methods. First, a survey involving an anonymous questionnaire (which included both the Fageström and Schneider tests), was conducted within a population of 276 students. Next, this was analyzed statistically using the Statystica 7.1 program. Results. The initial results of this research showed that 29.71% of all respondents smoke cigarettes. Moreover, the applied Fageström test revealed that the test population was either: slightly addicted (44,72% of all respondents), moderately addicted (34.84% of all respondents), or heavily addicted (17.44%). Conclusions. The prevalence of smoking among students of the Academy of Physical Education remains alarming. Furthermore, the negative health behaviors contribute to an adverse overview of the health of the questioned students.